Unified Application process in the development of a software to estimate inventory and growth-yield timber in eucalyptus plantations - García-Nieto, Moisés; Martínez-Trinidad, Tomás; de los Santos-Posadas, Héctor; Lugo-Espinosa, Oziel; Acosta-Mireles, Miguel; Arjona-Suarez, Enrique; Jiménez-Casas, Marcos (Instituto de Ecología, A.C., 2017)
A software was developed using the Unified Rational Process to estimate the inventory and wood growth/yield in commercial plantations of Eucalyptus, established in Las Choapas, Veracruz, Mexico. The software allows to estimate the inventory across samplings (random simply, random stratified and reason – regression) while the wood stock is projected by a system of equations of growth and performance. Modules allow to add, consult and eliminate information, as well as exporting it to Microsoft Excel. The software validation was made using the 2012 inventory, with 976 temporary sites and a total of 32 744 trees, distributed in 5896 ha, indicating a consistency between the results calculated by the company and the software. Besides, a quality test showed that 55% of the factors present a level of good quality and that 45% presents an acceptable one while 67% of the final users consider that the software has good quality and 33% express that it is acceptable.